BASICS OF INTERNAL BANKING AUDIT IN ROMANIA - BOGDAN RĂVAŞ (Annals of the University of Petrosani: Economics)
Internal audit should be a permanent function. In carrying out its duties and responsibilities, the bank's management should take all necessary measures so that the bank can always count on an adequate functioning of internal audit appropriate to the size of the bank and the nature of its operations. These measures include providing the internal audit department with adequate resources and staff to achieve its objectives.